(untitled) (Bangladesh Journal of Botany, 2024)
Effects of roadside cultivation of exotic Pennisetum purpureum on floristic composition and phytodiversity of wild vegetation in natural roadsides of Kaliganj upazila, Gazipur were studied during 2023 to 2024. A total of 117 vascular plant species comprising of 108 genera under 47 families have been recorded in natural roadside area and a total of 38 vascular plant species comprising of 36 genera under 18 families have been recorded in Pennisetum cultivated roadside area. In natural roadsides, maximum 97 species belonged to dicotyledons followed by 18 monocotyledons and 2 pteridophytic species. In Pennisetum cultivated roadsides, maximum 30 species belonged to dicotyledons followed by 6 monocotyledons and 2 pteridophytic species. In Pennisetum cultivated roadsides, maximum Shannon-Weiner diversity index was 2.02±0.05 and minimum index was 1.99±0.05. In natural roadsides, maximum Shannon-Weiner diversity index was 2.70±0.07 and minimum index was 2.43±0.04. Average Jackknife species richness 31.98 was found in Pennisetum cultivated roadsides, and 107.62 was found in natural roadsides. The collected data on the selected roadsides of Kaliganj upazila showed the trends of gradual decrease in floristic composition and phytodiversity status of Pennisetum cultivated roadsides in comparison to natural roadsides, which indicated that Pennisetum cultivation might have negative impacts on floristic composition and phytodiversity status of natural roadsides. Bangladesh J. Bot. 53(4): 913-922, 2024 (December)